Preparation method of ferromagnetic-antiferromagnetic coupled oxygen reaction catalyst with magnetic response

By using the iron magnetic-anti-iron magnetic coupling magnetic oxygen response catalyst preparation method in hydroladia, using targeted magnetic fields and ultrasonic solution technology to form nanosbarin bead-shaped metal boron-shaped metal and anti-iron magnetic nano-shaped metal hydroxide composite The heterogeneous structure solves the problem of improving the performance of catalyst in the existing technology, and has achieved high -efficiency electrolytic catalytic activity.

CN119332293APending Publication Date: 2025-01-21UNIV OF SCI & TECH LIAONING
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411614481.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

It is difficult to develop efficient and cost-effective catalysts for oxygen evolution reactions (OERs) in water electrolysis, while traditional methods improve catalytic performance while also difficult to solve the problems of uncontrollable and low yields during the preparation process.

Method used

A ferromagnetic-antiferromagnetic coupled magnetoresponsive oxygen reaction catalyst preparation method is used to dissolve metal salts and surfactants ultrasonically under a directional magnetic field, and then perform a reduction reaction with the assistance of a magnetic field to obtain ferromagnetic nanobead-shaped metal borides. , and through mechanical stirring and ion exchange with metal salts, an antiferromagnetic nanosheet metal hydroxide composite heterostructure grown on the surface of the nanobeads is formed.

Benefits of technology

The analysis of the oxygen reaction current in a mild magnetic field increased by 300%, significantly improved the catalytic activity of electrolyte, solved the problem of improvement of catalyst performance in traditional methods, and simplified the preparation process and improved controllability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119332293A_ABST
    Figure CN119332293A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a ferromagnetic-antiferromagnetic coupled oxygen reaction catalyst with magnetic response, and belongs to the technical field of catalysts.The preparation method comprises the steps that metal salt and a surfactant are dispersed in deionized water and ultrasonically dissolved, then a beaker is placed on a directional magnetic field, and at the moment, metal ions can be directionally arranged in the solution; dropwise adding the prepared sodium borohydride solution into the solution to reduce metal ions, and reducing at room temperature under the assistance of a magnetic field to obtain a ferromagnetic nano bead-like metal boride; the preparation method comprises the following steps: dispersing nano bead-like metal boride in an aqueous solution by adopting mechanical stirring, adding a small amount of metal salt, and carrying out ion exchange at room temperature to obtain an antiferromagnetic nano flaky metal hydroxide composite heterostructure grown on the surface of the nano bead; the method is simple and easy to control, efficient and large-scale preparation of the high-performance ferromagnetic-antiferromagnetic coupling material can be realized, and the problems of uncontrollability, low yield and the like in a ferromagnetic-antiferromagnetic preparation technology are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts, and in particular relates to a method for preparing a ferromagnetic-antiferromagnetic coupled magnetically responsive oxygen reaction catalyst. Background Art

[0002] The increase in global energy demand, coupled with the urgent need to mitigate climate change, has accelerated the development of sustainable and clean energy technologies as alternatives to fossil fuels. Hydrogen production from water electrolysis has emerged as a promising strategy for producing clean energy carriers, providing a path to decarbonize global industries such as energy, transportation, manufacturing, and agriculture. Accelerating the water electrolysis process is imperative when developing hydrogen energy infrastructure. One of the key tasks is to develop efficient and cost-effective catalysts for the oxygen evolution reaction (OER), which is a significant source of energy losses in water electrolysis. Transition metal hydroxides are candidate catalysts for OER because their multiple oxidation states can promote catalytic activity for oxygen reactions over a wide pH range.

[0003] At present, traditional methods of regulating metal hydroxides such as nanostructure, defect introduction, doping and phase change are used to improve the performance of OER electrocatalysts. However, these methods of improving the OER electrocatalytic performance of materials still cannot meet the needs of the industry. Theoretical analysis of catalytic materials and structures shows that the slow kinetics of OER is due to multiple electron transfers and spin state transitions between reactants and products, which is a kind of diamagnetic material (such as OH) - The quantum mechanical inhibition process of the conversion of ferromagnetic materials (or H2O) into paramagnetic oxygen molecules. Experimental studies have found that external magnetic fields can further enhance the OER performance of ferromagnetic materials, so constructing metal hydroxide materials that can respond magnetically under magnetic fields may improve their OER catalytic performance. However, metal hydroxides are antiferromagnetic in nature, and extremely high external magnetic fields must be used to improve the OER performance of metal hydroxides, but their yield is low. Summary of the invention

[0004] Based on the above technical problems, the present invention provides a method for preparing a ferromagnetic-antiferromagnetic coupled magnetically responsive oxygen reaction catalyst. The method of the present invention is simple and easy to control, and can realize the efficient and large-scale preparation of high-performance ferromagnetic-antiferromagnetic coupled materials, thereby solving the problems of uncontrollability and low yield existing in ferromagnetic-antiferromagnetic preparation technology.

[0005] The specific technical solution is: A method for preparing a ferromagnetic-antiferromagnetic coupled magnetically responsive oxygen reaction catalyst comprises the following steps: S1: Disperse the metal salt and surfactant in deionized water after O2 removal, dissolve them by ultrasonic for 10-30 minutes, and then place the beaker on a directional magnetic field, so that the metal ions can be arranged in a directional manner in the solution; S2: dripping the prepared sodium borohydride solution dropwise into the solution of step S1 to reduce the metal ions, and reducing the metal ions for 10-30 minutes at room temperature under the assistance of a magnetic field to obtain ferromagnetic nano-beaded metal borides; S3: The nano-beaded metal boride is dispersed in an aqueous solution by mechanical stirring, and a small amount of metal salt is added to perform ion exchange at room temperature for 0.5-2.0 hours to obtain a composite heterostructure of antiferromagnetic nano-sheet metal hydroxide grown on the surface of the nano-beaded metal boride.

[0006] In addition, the preparation method of a ferromagnetic-antiferromagnetic coupled magnetically responsive oxygen reaction catalyst in the above technical solution provided by the present invention may also have the following additional technical features: In the above technical solution, the metal boride reduced by the metal salt is a ferromagnetic substrate including cobalt boron, cobalt iron boron, cobalt nickel boron, cobalt iron nickel boron and cobalt iron nickel manganese boron nano-beaded metal boride.

[0007] In the above technical solution, the metal salt includes nitrates of nickel, cobalt, iron, and manganese, chlorides of nickel, cobalt, iron, and manganese, and sulfates of nickel, cobalt, iron, and manganese, and the concentration of the metal salt is 0.01-1.0 M.

[0008] In the above technical scheme, the surfactant is one of sodium polyacrylate, sucrose ester and polyvinyl pyrrolidone, the concentration of the surfactant solution is 0.01-0.5 M, the molar ratio of the surfactant to the metal salt is 0.01-4.0, the concentration of the sodium borohydride solution is 0.01-1.0 M, and the solvent is deionized water.

[0009] In the above technical solution, the magnetic field includes an alternating magnetic field, a constant magnetic field, a pulsating magnetic field, and a pulsed magnetic field, and the magnetic field strength is 0.1-1.0 T.

[0010] In the above technical solution, the ion exchange metal salt is one of cobalt, iron, nickel and manganese, and the ion exchange is performed for 0.5-3.0 hours at room temperature.

[0011] In the above technical scheme, the size of the nanobeads is controlled by surfactants. The size of the nanobeads is 20-500 nanometers, the length of the nanochain is 1-5 microns, and thin nanosheets of 100 nanometers grow on the surface of the nanobeads. The constructed heterostructure has a ferromagnetic metal boride core and an antiferromagnetic metal hydroxide shell. Under a mild magnetic field, the ferromagnetic-antiferromagnetic coupled catalyst can enhance the oxygen evolution reaction current by 300%, showing excellent catalytic activity for water electrolysis.

[0012] Compared with the prior art, the preparation method of the ferromagnetic-antiferromagnetic coupled magnetically responsive oxygen reaction catalyst of the present invention has the following beneficial effects: 1. The present invention uses magnetic field-induced synthesis of oriented ordered nano-beaded metal borides as the matrix, layered metal hydroxides as active sites, and constructs a ferromagnetic-antiferromagnetic coupling nano-heterostructure to obtain an efficient water electrolysis catalyst with enhanced OER catalytic activity by an external magnetic field.

[0013] 2. The present invention realizes the magnetic response of metal hydroxide in oxygen reaction by synthesizing ferromagnetic-antiferromagnetic coupled room temperature ferromagnetic heterostructures, and significantly enhances the intrinsic activity of oxygen evolution reaction by designing metal boride / oxyhydroxide system with controllable heterostructures. Metal boride / oxyhydroxide exhibits excellent catalytic performance in water electrolysis, achieving a catalytic activity one order of magnitude higher than that in the absence of magnetic field under a mild magnetic field, surpassing the existing metal hydroxide oxygen reaction catalysts.

[0014] 3. The method of the present invention is simple and easy to control, and can realize the efficient and large-scale preparation of high-performance ferromagnetic-antiferromagnetic coupling materials, solving the problems of uncontrollability and low yield in ferromagnetic-antiferromagnetic preparation technology.

[0015] 4. The present invention can synthesize materials with unique ferromagnetic nano-bead structure by using only magnets. These nano-beads have superparamagnetism and can grow antiferromagnetic nanosheets to form unique ferromagnetic-antiferromagnetic coupling materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is a transmission electron microscope image of the ferromagnetic metal boride nanobeads prepared in Example 2 of the present invention; Figure 2 This is a transmission electron microscopy image of the heterostructure of ferromagnetic metal boride and antiferromagnetic metal boride prepared in Example 3 of the present invention; Figure 3 The ferromagnetic and ferromagnetic-antiferromagnetic coupling prepared in Example 4 of the present invention are curves of changes in magnetic field and magnetic susceptibility; Figure 4 The relationship curves between temperature and magnetic susceptibility of ferromagnetism, antiferromagnetism and ferromagnetism-antiferromagnetism coupling prepared in Example 4 of the present invention under a constant magnetic field; Figure 5 This is a real-time graph of electrode surface changes under the assistance of a magnetic field when a ferromagnetic-antiferromagnetic coupling catalyst is prepared in Example 5 of the present invention; Figure 6 The catalytic performance of the ferromagnetic metal boride prepared in Example 5 of the present invention as an oxygen reaction catalyst in the presence or absence of a magnetic field and its Tafel slope diagram; Figure 7 The chronoelectric current curve of the ferromagnetic-antiferromagnetic coupling heterostructure prepared in Example 5 of the present invention as an oxygen reaction catalyst in the presence or absence of a magnetic field; Figure 8Catalytic performance of the ferromagnetic-antiferromagnetic coupled heterostructure prepared in Example 5 of the present invention as an oxygen reaction catalyst in the presence or absence of a magnetic field and its Tafel slope diagram. DETAILED DESCRIPTION

[0017] The following is a combination of specific implementation cases and attached Figure 1-8 The present invention is further described below, but the present invention is not limited to these embodiments. Embodiment 1:

[0018] A method for preparing a ferromagnetic-antiferromagnetic coupled magnetically responsive oxygen reaction catalyst comprises the following steps: S1: Disperse the metal salt and surfactant in deionized water after O2 removal, dissolve them by ultrasonic for 10-30 minutes, and then place the beaker on a directional magnetic field, so that the metal ions can be arranged in a directional manner in the solution; S2: dripping the prepared sodium borohydride solution dropwise into the solution of step S1 to reduce the metal ions, and reducing the metal ions for 10-30 minutes at room temperature under the assistance of a magnetic field to obtain ferromagnetic nano-beaded metal borides; S3: The nano-beaded metal boride is dispersed in an aqueous solution by mechanical stirring, and a small amount of metal salt is added to perform ion exchange at room temperature for 0.5-2.0 hours to obtain a composite heterostructure of antiferromagnetic nano-sheet metal hydroxide grown on the surface of the nano-beaded metal boride.

[0019] In an embodiment of the present invention, the metal boride reduced by the metal salt is a ferromagnetic substrate including cobalt boron, cobalt iron boron, cobalt nickel boron, cobalt iron nickel boron and cobalt iron nickel manganese boron nano-beaded metal boride.

[0020] In an embodiment of the present invention, the metal salt includes nitrates of nickel, cobalt, iron, and manganese, chlorides of nickel, cobalt, iron, and manganese, and sulfates of nickel, cobalt, iron, and manganese, and the concentration of the metal salt is 0.01-1.0 M.

[0021] In an embodiment of the present invention, the surfactant is one of sodium polyacrylate, sucrose ester and polyvinyl pyrrolidone, the concentration of the surfactant solution is 0.01-0.5 M, the molar ratio of the surfactant to the metal salt is 0.01-4.0, the concentration of the sodium borohydride solution is 0.01-1.0 M, and the solvent is deionized water.

[0022] In an embodiment of the present invention, the magnetic field includes an alternating magnetic field, a constant magnetic field, a pulsating magnetic field, and a pulsed magnetic field, and the magnetic field strength is 0.1-1.0 T.

[0023] In an embodiment of the present invention, the ion exchange metal salt is one of cobalt, iron, nickel and manganese, and the ion exchange is performed for 0.5-3.0 hours at room temperature.

[0024] In an embodiment of the present invention, the size of the nanobeads is controlled by a surfactant, the size of the nanobeads is 20-500 nanometers, the length of the nanochain is 1-5 microns, and 100-nanometer thin nanosheets grow on the surface of the nanobeads. The constructed heterostructure has a ferromagnetic metal boride core and an antiferromagnetic metal hydroxide shell. Under a mild magnetic field, the ferromagnetic-antiferromagnetic coupled catalyst can enhance the oxygen evolution reaction current by 300%, showing excellent catalytic activity for water electrolysis. Embodiment 2:

[0025] A1: 0.7 mmol of cobalt chloride hexahydrate and 0.4 mmol of sodium dodecylamine were dissolved in 100 mL of deionized water from which O2 had been removed; then, a freshly prepared sodium borohydride solution (50 mg in 40 mL) was added dropwise as a reducing agent; during the reduction reaction, the induced magnetic field was maintained at 100 mT, and the resulting product was extracted using a magnet, thoroughly washed with deionized water to remove impurities, and then freeze-dried to obtain beaded cobalt-boron nanomaterials; A2: 100 mg of the beaded cobalt-boron nanomaterial prepared in step A1 was dispersed in 100 mL of deionized water, and then 2 mmol of cobalt chloride hexahydrate was dissolved in the mixture; the suspension was then mechanically stirred at 200 rpm for 1 hour; the resulting product was washed with deionized water several times, and then dried in a vacuum oven at 40°C for 12 hours. After the reaction was completed, a black powder of cobalt-boron / cobalt hydroxide was obtained; A3: The ferromagnetic-antiferromagnetic coupled cobalt boron / cobalt hydroxide heterostructure material prepared in step A2 is prepared as a membrane electrode, and its catalytic activity in oxygen reaction is evaluated with the assistance of an external magnetic field; the results show that ferromagnetic-antiferromagnetic metal hydroxides can significantly enhance the current density of oxygen evolution reaction under a mild magnetic field, showing excellent catalytic activity in water electrolysis. Embodiment 3:

[0026] B1: 0.1 mmol of cobalt chloride hexahydrate, 0.1 mmol of nickel chloride hexahydrate and 0.4 mmol of polyvinyl pyrrolidone were dissolved in 100 mL of deionized water from which O2 had been removed; then, a freshly prepared sodium borohydride solution (50 mg in 40 mL) was added dropwise as a reducing agent; during the reduction reaction, an induced magnetic field of 100 mT was maintained, and the resulting product was extracted using a magnet, thoroughly washed with deionized water to remove impurities, and then freeze-dried to obtain beaded cobalt-nickel-boron nanomaterials; B2: Disperse 100 mg of the beaded cobalt-nickel-boron nanomaterial prepared in step B1 in 100 mL of deionized water, and then dissolve 2 mmol of cobalt chloride hexahydrate into the mixture; then mechanically stir the suspension at 200 rpm for 1 hour; wash the resulting product with deionized water, and then dry it in a vacuum oven at 40°C for 12 hours; after the reaction is completed, a black powder of cobalt-nickel-boron / cobalt-nickel hydroxide is obtained.

[0027] B3: The ferromagnetic-antiferromagnetic coupled cobalt-nickel-boron / cobalt-nickel hydroxide heterostructure material prepared in step B2 is prepared as a membrane electrode, and its catalytic activity in oxygen reaction is evaluated using an external magnetic field; the results show that ferromagnetic-antiferromagnetic metal hydroxides can significantly enhance the current density of oxygen evolution reaction under a mild magnetic field, showing excellent catalytic activity in water electrolysis. Embodiment 4:

[0028] C1: 0.1 mmol cobalt chloride hexahydrate, 0.1 mmol iron sulfate heptahydrate and 0.4 mmol sodium polyacrylate were dissolved in 100 mL of deionized water from which O2 had been removed; then, a freshly prepared sodium borohydride solution (50 mg in 40 mL) was added dropwise as a reducing agent; during the reduction reaction, the induced magnetic field was maintained at 100 mT, and the resulting product was extracted using a magnet, thoroughly washed with deionized water to remove impurities, and then freeze-dried to obtain beaded cobalt iron boron nanomaterials; C2: 100 mg of the cobalt iron boron nanobeads prepared in step C1 were dispersed in 100 mL of deionized water, and then 2 mmol of cobalt chloride hexahydrate was dissolved in the mixture; the suspension was mechanically stirred at 200 rpm for 1 hour; the resulting product was washed with deionized water and then dried in a vacuum oven at 40° C. for 12 hours; after the reaction was completed, a black powder of cobalt iron boron / cobalt iron hydroxide was obtained; C3: The ferromagnetic-antiferromagnetic coupled cobalt-iron-boron / cobalt-iron hydroxide heterostructure material prepared in step C2 is prepared as a membrane electrode, and its catalytic activity in oxygen reaction is evaluated using an external magnetic field; the results show that ferromagnetic-antiferromagnetic metal hydroxides can significantly enhance the current density of oxygen evolution reaction under a mild magnetic field, showing excellent catalytic activity in water electrolysis. Embodiment 5:

[0029] D1: 0.08 mmol cobalt chloride hexahydrate, 0.08 mmol nickel chloride hexahydrate, 0.04 mmol ferric sulfate heptahydrate and 400 mg polyvinyl pyrrolidone were dissolved in 100 mL of deionized water from which O2 had been removed; then, a freshly prepared sodium borohydride solution (50 mg in 40 mL) was added dropwise as a reducing agent; during the reduction reaction, the induced magnetic field was maintained at 100 mT, and the resulting product was extracted using a magnet, thoroughly washed with deionized water to remove impurities, and subsequently freeze-dried to obtain beaded cobalt-iron-nickel-boron nanomaterials.

[0030] D2: 100 mg of the cobalt-iron-nickel-boron nanobeads prepared in step D1 were dispersed in 100 mL of deionized water, and then 2 mmol of cobalt chloride hexahydrate was dissolved in the mixture; the suspension was mechanically stirred at 200 rpm for 1 hour; the obtained product was washed with deionized water, and then dried in a vacuum oven at 40° C. for 12 hours; after the reaction was completed, a black powder of cobalt-iron-nickel-boron / cobalt-iron-nickel-boron hydroxide was obtained; D3: The ferromagnetic-antiferromagnetic coupled cobalt-iron-nickel-boron / cobalt-iron-nickel-boron hydroxide heterostructure material prepared in step D2 was prepared as a membrane electrode, and its catalytic activity in oxygen reaction was evaluated using an external magnetic field. The results show that ferromagnetic-antiferromagnetic metal hydroxides can significantly enhance the current density of oxygen evolution reaction under a mild magnetic field, showing excellent catalytic activity in water electrolysis.

[0031] According to Examples 1-5, the present invention has the following characteristics: The present invention uses magnetic field-induced synthesis of oriented ordered nano-beaded metal borides as a matrix, layered metal hydroxides as active sites, and constructs a ferromagnetic-antiferromagnetic coupling nano-heterostructure to obtain an efficient water electrolysis catalyst with enhanced OER catalytic activity by an external magnetic field.

[0032] The present invention realizes the magnetic response of metal hydroxide in oxygen reaction by synthesizing ferromagnetic-antiferromagnetic coupled room temperature ferromagnetic heterostructure, and significantly enhances the intrinsic activity of oxygen evolution reaction by designing metal boride / oxyhydroxide system with controllable heterostructure. Metal boride / oxyhydroxide exhibits excellent catalytic performance in water electrolysis, and achieves catalytic activity one order of magnitude higher than that in the absence of magnetic field under mild magnetic field, surpassing existing metal hydroxide oxygen reaction catalysts.

[0033] The method of the invention is simple and easy to control, and can realize the efficient and large-scale preparation of high-performance ferromagnetic-antiferromagnetic coupling materials, thereby solving the problems of uncontrollability and low yield existing in the ferromagnetic-antiferromagnetic preparation technology.

[0034] The invention can synthesize materials with unique ferromagnetic nano-bead structure by using only magnets. These nano-beads have superparamagnetism and can grow antiferromagnetic nano-sheets to form unique ferromagnetic-antiferromagnetic coupling materials.

[0035] The ferromagnetic-antiferromagnetic coupled catalyst of the present invention can enhance the oxygen evolution reaction current by 300% under a mild magnetic field, showing excellent catalytic activity for water electrolysis.

[0036] In the description of the present invention, the term "plurality" refers to two or more than two. Unless otherwise clearly defined, the orientation or positional relationship indicated by the terms "upper" and "lower" is based on the orientation or positional relationship shown in the drawings. It is only for the convenience of describing the present invention and simplifying the description, and does not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation. Therefore, it cannot be understood as a limitation on the present invention. The terms "connection", "installation", "fixation", etc. should be understood in a broad sense. For example, "connection" can be a fixed connection, a detachable connection, or an integral connection; it can be directly connected or indirectly connected through an intermediate medium. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0037] In the description of the present invention, the description of the terms "one embodiment", "some embodiments", "specific embodiments", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In the present invention, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0038] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a ferromagnetic-antiferromagnetic coupled magnetically responsive oxygen reaction catalyst, characterized in that: The steps include: S1: Disperse the metal salt and surfactant in deionized water after O2 removal, dissolve them by ultrasonic for 10-30 minutes, and then place the beaker on a directional magnetic field, so that the metal ions can be arranged in a directional manner in the solution; S2: dripping the prepared sodium borohydride solution dropwise into the solution of step S1 to reduce the metal ions, and reducing the metal ions for 10-30 minutes at room temperature under the assistance of a magnetic field to obtain ferromagnetic nano-beaded metal borides; S3: The nano-beaded metal boride is dispersed in an aqueous solution by mechanical stirring, and a small amount of metal salt is added to perform ion exchange at room temperature for 0.5-2.0 hours to obtain a composite heterostructure of antiferromagnetic nano-sheet metal hydroxide grown on the surface of the nano-beaded metal boride.

2. The method for preparing a ferromagnetic-antiferromagnetic coupled magnetically responsive oxygen reaction catalyst according to claim 1, characterized in that: The metal boride reduced by the metal salt is a ferromagnetic base metal boride including cobalt boron, cobalt iron boron, cobalt nickel boron, cobalt iron nickel boron and cobalt iron nickel manganese boron nano-beaded metal boride.

3. The method for preparing a ferromagnetic-antiferromagnetic coupled magnetically responsive oxygen reaction catalyst according to claim 1, characterized in that: The metal salts include nitrates of nickel, cobalt, iron, and manganese, chlorides of nickel, cobalt, iron, and manganese, and sulfates of nickel, cobalt, iron, and manganese, and the concentration of the metal salts is 0.01-1.0 M.

4. The method for preparing a ferromagnetic-antiferromagnetic coupled magnetically responsive oxygen reaction catalyst according to claim 1, characterized in that: The surfactant is one of sodium polyacrylate, sucrose ester and polyvinyl pyrrolidone, the concentration of the surfactant solution is 0.01-0.5 M, the molar ratio of the surfactant to the metal salt is 0.01-4.0, the concentration of the sodium borohydride solution is 0.01-1.0 M, and the solvent is deionized water.

5. The method for preparing a ferromagnetic-antiferromagnetic coupled magnetically responsive oxygen reaction catalyst according to claim 1, characterized in that: The magnetic field includes alternating magnetic field, constant magnetic field, pulsating magnetic field and pulsed magnetic field, and the magnetic field intensity is 0.1-1.0T.

6. The method for preparing a ferromagnetic-antiferromagnetic coupled magnetically responsive oxygen reaction catalyst according to claim 1, characterized in that: The ion exchange metal salt is one of cobalt, iron, nickel and manganese, and the ion exchange is performed for 0.5-3.0 hours at room temperature.

7. The method for preparing a ferromagnetic-antiferromagnetic coupled magnetically responsive oxygen reaction catalyst according to claim 1, characterized in that: The size of the nanobeads is controlled by surfactants. The size of the nanobeads is 20-500 nanometers, and the length of the nanochain is 1-5 microns. Thin nanosheets of 100 nanometers grow on the surface of the nanobeads. The constructed heterostructure has a ferromagnetic metal boride core and an antiferromagnetic metal hydroxide shell. Under a mild magnetic field, the ferromagnetic-antiferromagnetic coupled catalyst can enhance the oxygen evolution reaction current by 300%, showing excellent catalytic activity for water electrolysis.